PENGARUH METODE AL-QOSIMI TERHADAP KEMAMPUAN MENGHAFAL AL-QUR’AN SISWA KELAS VII MTS BAITUN NAJAH KARANGANYAR 2024/2025 - Ganjar Cahyono; Syamsudin Syamsudin (Jurnal Manajemen Pendidikan, 2026)
Purpose: This study examines the implementation of the Al-Qosimi method and its effect on students’ Qur’an memorization ability in Grade VII at MTs Baitun Najah Karanganyar.  Method: A quantitative correlational design was employed. The sample consisted of 29 seventh-grade students. Data on Al-Qosimi method implementation were collected using a 15-item questionnaire, while memorization ability was taken from tahfidz performance documentation. Instrument testing indicated all items were valid and reliable (Cronbach’s Alpha = 0.949). Data were analyzed using Pearson correlation, Spearman correlation (as a non-parametric reinforcement), and simple linear regression. Results: Pearson correlation showed a negative low relationship (r = –0.263; Sig. = 0.167), indicating no statistically significant association between the Al-Qosimi method and memorization ability. Spearman’s rho also showed a very weak negative relationship (ρ = –0.039; Sig. = 0.841). Regression results confirmed the non-significant effect (t = –1.419; Sig. = 0.167) with the model Y = 93.915 – 0.284X. Implications: The findings imply that improving Qur’an memorization outcomes may require strengthening supporting factors beyond the method itself, such as students’ motivation, consistency of muroja’ah at home, baseline reading proficiency, and structured monitoring.